Construct validity of the Herth Hope Index: A systematic review - Dehghan Nayeri, Nahid; Goudarzian, Amir Hossein; Herth, Kaye; Naghavi, Navaz; Sharif Nia, Hamid; Yaghoobzadeh, Ameneh; Pahlevan Sharif, Saeed; Allen, Kelly-Ann (International Journal of Health Sciences, 2020)
Objective: The psychological construct of hope is an important determinant for mental health and well-being. The availability of valid and reliable instruments to measure hope is therefore critical. Despite a large number of psychometric studies on the Herth Hope Index (HHI), its construct validity has not yet been determined. Therefore, this paper aimed to conduct a systematic review of the psychometric properties of the HHI. Method: Databases such as PubMed, Science Direct, Google Scholar, Magiran, SID, IranDoc, and IranMedex, were evaluated systematically using the terms “Herth Hope Index”, “psychometric”, “validity”, “reliability”, and related terms (with the use of OR and AND operators) and no restrictions on the year of publication. A total of 13 eligible studies were found published between 1992 and 2018 in the USA, Portugal, Switzerland, Iran, Germany, Petersburg, Japan, the Netherlands, Lima, Peru, and Norway. The methodology used in the available studies included principle component analysis (N = 6), maximum likelihood estimation (N = 5), and principal axis factoring (N = 1).One study didn’t point the methodology. Results: Four studies reported the total extracted variances to be less than 50%, six studies reported variance between 50% and 60%, and three papers reported variance that exceeded 60%. Of the papers that examined the factor structure of the HHI, two studies reported a one-factor solution, seven reported two factors, and four reported a three-factor solution. Although the HHI is the most widely translated and psychometrically tested tool in languages other than English, psychometric variations in factor solutions remain inconsistent. Conclusion: Findings highlight the need for future research that appraises the validity of the HHI in different countries, and how the measure relates to other scales that evaluate hope.